New synthesis of oligosaccharides modelling the M epitope of the Brucella O-polysaccharide - Tsvetkov, Yury E.; Volkov, Timur M.; Eremin, Sergei A.; Sklyarov, Oleg D.; Kulakov, Yuri K.; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Chemistry, 2024)
Brucellosis is a dangerous zoonotic disease caused by bacteria of the genus Brucella. Diagnosis of brucellosis is based on the detection in animal and human sera of antibodies to the Opolysaccharide of Brucella lipopolysaccharide. The currently employed serodiagnosis of brucellosis relies on the use of the Brucella O-polysaccharide as a diagnostic antigen. However, the existence of bacterial species, which also express O-polysaccharides structurally similar to that of Brucella, may decrease the specificity of the brucellosis detection due to false-positive test results. It has been shown that the efficiency of the test can be significantly improved by using synthetic oligosaccharides that correspond to the so-called M epitope of the Brucella O-antigen. This epitope is characterized by an α-(1→3)-linkage between D-perosamine units and is unique to Brucella. Here we report on an efficient approach to the synthesis of oligosaccharides that model the M epitope of the Brucella O-polysaccharide. The approach is based on the use of the α-(13)-linked disaccharide thioglycoside as the key donor block. Its application allowed the straightforward assembly of a set of four protected oligosaccharides, which includes a disaccharide, two trisaccharides, and a tetrasaccharide, in five glycosylation steps. The synthesized oligosaccharides are planned to be used in the development of diagnostic tools for identifying brucellosis in humans and domestic animals, as well as a potential vaccine against it.